Effect of glaucoma and cataract on daily activities in patients with sarcopenic obesity - A.E. Kopylov; N.M. Agarkov; M.V. Alymova (РМЖ "Клиническая офтальмология", 2024)
A.E. Kopylov1, N.M. Agarkov1–3, M.V. Alymova2 1Tambov Branch of the S. Fyodorov Eye Microsurgery Federal State Institution, Tambov, Russian Federation 2Southwestern State University, Kursk, Russian Federation 3Belgorod State National Research University, Belgorod, Russian Federation Aim: to evaluate the effect of glaucoma and cataract on activities of daily living in elderly patients with sarcopenic obesity (SO). Patients and Methods: the study included 128 patients with cataract and SO and 125 age-matched patients with glaucoma and SO. All patients underwent a comprehensive clinical and instrumental ophthalmic examination. To assess activities of daily living, we used our own 8-question test. Results: the effect of cataract and SO causing total dependence on others was more significant (12.18 points) than that of glaucoma and SO causing moderate dependence (10.18 points, p<0.01). The groups were also characterized by significant differences in all activities of daily living, including needle threading and nail clipping. In particular, limitations in needle threading were estimated at 1.84±0.03 points in patients with cataract and SO, which was significantly higher than in patients with glaucoma and SO (1.52±0.02 points, p<0.01). A similar pattern was found for nail clipping (1.75±0.03 points and 1.43±0.04 points, respectively, p<0.01). Factor analysis of the effect of cataract and SO and glaucoma and SO showed the highest factor loading on the development of dependency on others for needle threading (0.829 and 0.572 respectively) and nail clipping (0.807 and 0.469 respectively) in both groups. However, the effect of cataract and SO on the development of limitations in these activities of daily living is more significant than the effect of glaucoma and SO. Conclusions: among age-related eye diseases in elderly patients, cataract and SO significantly limit daily activities. Keywords: glaucoma, cataract, sarcopenic obesity, activities of daily living, basic functional activity, elderly. For citation: Kopylov A.E., Agarkov N.M., Alymova M.V. Effect of glaucoma and cataract on daily activities in patients with sarcopenic obesity. Russian Journal of Clinical Ophthalmology. 2024;24(1):14–18 (in Russ.). DOI: 10.32364/2311-7729-2024-24-1-3.